Clinical characteristics of newborns with the deafness-associated GJB2 variant p.V37I in Changzhi, China - Ruijie Feng; Ernest Mangantig; wan shahriman yushdie wan yusoff; khairil anuar md isa; Zhipeng Hu; Xiaoze Li; Mohd Nazri Abu (Journal of Clinical and Health Sciences, 2026)
Background: Hearing loss affects over 430 million people globally, with genetic factors accounting for at least 50% of congenital cases. The GJB2 gene mutations are the most common cause of non-syndromic hearing impairment (NSHI) worldwide, but the clinical characteristics of c.109G>A (p.V37I) mutation in the GJB2 gene are still indistinct. Objective: To evaluate the prevalence and clinical impact of the c.109G>A (p.V37I) mutation in the GJB2 gene among neonates through audiological and genetic tests. Methods: A cohort of 848 neonates was enrolled between February 2022 and February 2024. All subjects underwent hearing screening and deafness genetic screening for 7 hotspot variants in the GJB2 gene (c.109G>A, c.35delG, c.176_191del16, c.235delC, c.299_300delAT, c.79G>A, and c.341A>G). The association between c.109G>A genotype and hearing phenotype was assessed. Results: The c.109G>A mutation was identified in 24 individuals (2.83%), including 11 heterozygotes, 12 compound heterozygotes, and one homozygote. Audiological test failure rates were significantly higher in c.109G>A carriers compared to non-carriers (18.2% vs. 0.7%, P < 0.001). The homozygous proband exhibited confirmed bilateral hearing loss, and a significant association was observed between genotype and hearing outcomes overall (P = 0.003). Conclusion: This study assessed the prevalence of GJB2 mutations in a Changzhi neonatal cohort. The results demonstrate a significant association between the c.109G>A variant and an increased risk of hearing loss, particularly in homozygous and compound heterozygous carriers. These findings demonstrate that GJB2 variant p.V37I is significantly associated with neonatal hearing loss, underscoring its importance for inclusion in genetic screening programs to facilitate early intervention.